THE ROLE OF IFN- γ AND TNF- α IN EXPERIMENTAL MASTITIS - & et al, Touma (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was design to characterize the immune response in experimentally Pseudomonas aeruginosa mastitis mice treated probiotic bifidocin and cazacin of Bifidobacterium spp. and Lactobacillus casei. We quantified the level of the IFN-γ and TNF-α cytokines in blood by ELISA technique. IFN-γ level was significantly higher in infected group compared to control (340.21 ± 41.61, 8.45 ± 0.83 pg/ml, respectively). While the level of IFN-γ was significantly higher in mastitis mice than bifidocin and cazacin treated mice. Also, TNF-α level showed a significant increase in mastitis mice compared to controls (320.11±40.33, 8.45±0.83pg/ml, respectively). Among mastitis and bifidocin (9 and 18 mg/ml), cazacin (11 and 22 mg/ml) treated mice a high level of TNF-α was observed in these groups without variant significant differences. These suggest that Pseudomonas aeruginosa caused mice's mastitis developed a cell-mediated response. In addition, the extracts of bifidocin and cazacin have a possibility to use in treatment and prevention of mastitis infections and able to modulate the levels of cytokines in lactating mice.